El Barón de Verulam y el vulgo - Solano Villareal, Diana (2017)
This article focuses itself on Francis Bacon’s position concerning common people, from the point of view of New Atlantis, Novum Organum, Instauratio Magna and On Selfish Wisdom. In this paper we invoke the Decolonial Modernity/Coloniality theoretical perspective, specially Professor Bernal Herrera Montero’s Theory of Bipolar Modernity. Our paper explains how common people was seen, by Francis Bacon, as harmful for the advancement of learning.